Detecting epithelial-mesenchymal transition signaling molecules in cervical epithelial cells aids in the early diagnosis of cervical lesions - Zhanfeng Zhang; Chuanzhen Xie; Rong Zhao; Shuai Wang; Zaichun Xie; Zhiyu Pang; Qian Xu; Peng Zhang; Yuanrui Liu (BMC Cancer)
Abstract Background This study aimed to investigate the potential utility of Epithelial-mesenchymal transition (EMT) signaling cell detection in the early diagnosis of cervical lesions. Methods Enrichment of cervical epithelial cells was carried out using a calibrated membrane with 8-μm diameter pores. RNA-in situ hybridization (RNA-ISH) was employed to detect and characterize EMT cells utilizing specific EMT markers. Results EMT cells were successfully identified in cervical samples, while none were detected in the healthy control group. Meanwhile, the number of EMT cells is not correlated with either the presence or type of HPV infection. Comparison of diagnostic tests showed the area under the curve (AUC) for HPV DNA tests, Thinprep cytologic tests (TCT), colposcopy and EMT signaling tests to be 0.758, 0.800, 0.889 and 0.992, respectively. A higher detection rate of EMT cells was observed in patients with cervical lesions aged ≥ 45 compared to those aged < 45 years (P < 0.05). In cervical cancer patients, a significantly greater number of EMT cells were found in FIGO stage II than in FIGO stage I (P < 0.05). Notably, epithelial-type EMT cells were detected at significantly higher rates in patients with high-grade squamous intraepithelial lesion (HSIL) and cervical cancer compared to those with low-grade squamous intraepithelial lesion (LSIL). Conclusions EMT markers demonstrate potential as effective tools for detecting cervical lesions.